Subprodutos da filetagem de tilápias (OreochromisNiloticus) na elaboração de surimi e silagem ácida - Gomes, Ana Cristina de Souza (2012)
Surimi and acid silage of fish are ancient techniques of waste recovery and preservation of organic matter. With the aim of characterizing these two products, physico-chemical and instrumental analysis were made, in order to contribute with the improvement of the quality of both. Thus, we prepared two papers: the first featured at 0, 10, 20 and 35 days, acidic silages prepared with filleting waste of Nile tilapia (Oreochromis niloticus) plus 3% w/w of formic acid, phosphoric, hydrochloric and sulfuric acids, alone or combined in different proportions. Under the conditions in which the experiment was conducted, it was found that the storage interfered in the analysis of the physico-chemical variables, stability was observed in moisture, reduction in protein and lipids and increased levels of ash, calcium and phosphorus. The second study characterized surimis filleting wastes produced with Nile tilapia (Oreochromis niloticus) and diferenes cryoprotectants (sorbitol, sucrose and banana flour) and different protease inhibitors (egg albumin and whey protein). The results indicated that sucrose, like protease inhibitor and whey protein, were the combination that gave the best results in terms of moisture, protein, shear force and gel stregnth. On the other hand, banana flour and egg albumin significantly changed the color of the prepared surimis.